Does Prayer Have a Place in Nursing Care? - French, Charlotte (2009)
Following a thorough evaluation and analysis of the current literature, this literature review aimed to enlighten the reader on the benefits, problems, issues and implications of including prayer for patients in the role of the nurse. The inclusion of religion and prayer within nursing care is not a new phenomenon and spirituality has played a part in healthcare since ancient times. However, research studies into the effects of intercessory prayer have provided inconclusive results due to their abundant methodological, theological and ethical limitations. As this review highlights, there are ethical problems surrounding the use of prayer in nursing practice. There are also practical issues, including; how a nurse should pray, the appropriate actions of a nurse who does not wish to pray, the education of nurses, how a nurse should assess a patient in terms of spirituality. This literature review concludes that whilst the use of intercessory prayer as a medical intervention for physical illness may be premature, the use of prayer as a means of enabling a patient to express their spirituality and/or connect with a Divine Being is both appropriate and professional providing the nurse in question adheres to basic ethical principles whilst using intuition and sensitivity.